2018
DOI: 10.1073/pnas.1805039115
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant early endosome biogenesis mediates complement activation in the retinal pigment epithelium in models of macular degeneration

Abstract: Abnormally enlarged early endosomes (EEs) are pathological features of neurodegenerative diseases, yet insight into the mechanisms and consequences of EE expansion remains elusive. Here, we report swollen apical EEs in the retinal pigment epithelium (RPE) of aged human donors and in the pigmented mouse model of Stargardt early-onset macular degeneration. Using high-resolution live-cell imaging, we show that age-related and pathological accumulation of lipofuscin bisretinoids increases ceramide at the apical su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 39 publications
(62 reference statements)
4
85
0
Order By: Relevance
“…Although a majority of cargos are transported in this manner, there appears to be some variability, perhaps indicating a degree of flexibility which could help RPE to cope with stressful conditions. The importance of correct cargo trafficking and timely proteolytic degradation is demonstrated by evidence from diverse neurodegenerative and storage diseases which reveal impairment of these mechanisms in early stages of pathology . Our studies reveal divergent outcomes for POS trafficking under conditions of oxidative stress, impaired lysosomal function and disrupted autophagy ( Figure ), all of which can occur simultaneously in the senescent RPE .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although a majority of cargos are transported in this manner, there appears to be some variability, perhaps indicating a degree of flexibility which could help RPE to cope with stressful conditions. The importance of correct cargo trafficking and timely proteolytic degradation is demonstrated by evidence from diverse neurodegenerative and storage diseases which reveal impairment of these mechanisms in early stages of pathology . Our studies reveal divergent outcomes for POS trafficking under conditions of oxidative stress, impaired lysosomal function and disrupted autophagy ( Figure ), all of which can occur simultaneously in the senescent RPE .…”
Section: Discussionmentioning
confidence: 75%
“…Enlarged endosomes is a known feature of early stages of neuropathological conditions such as Alzheimer's disease and Down syndrome where misfolded proteins principally localize to Rab5 vesicles . Swollen endosomes are also reported in RPE of aged human donors and Abca4 −/− mouse model of Stargardt disease . The failure of POS cargos to reach terminal stages of the proteolytic pathway could lead to their accumulation in RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have reported that the age-related and pathological accumulation of lipofuscin bisretinoids (composed of A2E and other vitamin A metabolites) in macular degenerations leads to a secondary accumulation of cholesterol in the RPE (13)(14)(15)52). We therefore asked if the increased mobility of ApoE3 and ApoE4 vesicles mitigates the cholesterol storage seen in RPE with A2E.…”
Section: Rpementioning
confidence: 94%
“…To avoid these potentially confounding issues, we chose to employ our well-characterized polarized adult primary porcine RPE cultures (40) transfected with fluorescently-tagged human ApoE2, E3 or E4 to investigate the functions of ApoE isoforms in the RPE. We have extensively used this model for live-cell imaging and have shown that it recapitulates critical disease phenotypes observed in human donor RPE and in mouse models of Stargardt inherited macular degeneration including lipofuscin-induced cholesterol accumulation, and consequent autophagic defects and complement-mediated mitochondrial injury (13)(14)(15). Pertinently, porcine APOE has a promoter polymorphism that decreases endogenous ApoE expression (41).…”
Section: Polarized Adult Primary Rpe Model For Investigating Isoform-mentioning
confidence: 99%
See 1 more Smart Citation